Objetivos do Desenvolvimento Sustentável e o tráfico de pessoas no Brasil: progressos e desafios na implementação de políticas públicas - Dominguez, Brenda de Paula Mendes (2023)
The Sustainable Development Goals (SDGs), launched as a guide for the international development agenda, represented an advance in terms of the centrality of the individual as part of the balance between the environment and society, by establishing freedom and human rights as essential for individuals to take part in the development process. In this scenario, phenomena whose core is anchored in exploitative practices, such as human trafficking, gained even more strength and relevance when included as specific goals of the SDGs. Mentioned more specifically in target 8.7, human trafficking is characterized as a phenomenon whose possibilities for combating it tend to expand as they benefit from the indivisibility and mutuality of the goals, as it is a problem that is interrelated, above all, with the layout of the labor market, social inequality and poverty. Given this scenario of deprivation, it is considered that it is essential to understand freedom in terms of capacity, as the core of the development process in this new agenda, and, consequently, to value the agentic condition of individuals in their social contexts, as well as the provision of accessible opportunities. This research, therefore, aims to answer the following question: how were the SDGs connected to combating human trafficking and influenced the implementation of the III National Plan to Combat Trafficking in Persons; with the general objective: to analyze the correlation between human trafficking and the SDGs, in light of Amartya Sen's propositions. In the first chapter, the evolution of human trafficking will be described based on its main international normative frameworks; the second chapter will relate the SDGs to human trafficking in light of Amartya Sen's propositions, in order to demonstrate the potential of the Capabilities Approach (CA) to analyze human trafficking as part of the development agenda and also its limitations and; the third chapter will report the influence of the SDGs on the implementation and monitoring of the III PNETP. Finally, this research will consider the influence of the SDGs on the implementation of the III PNETP as a major advance in terms of sharing technical knowledge between the institutions involved, presenting considerable advances in terms of monitoring, strengthening institutional relationships and the principle of creating channels of more fluid information, even in the midst of an adverse political scenario.